Response of Muscle Damage Indices to Short-term Supplementation of HMB-FA in Professional Soccer Players (Journal of Pharmaceutical Negative Results, 2022)
Allergic rhinitis (AR) is an IgE-mediated disorder triggered when the immune system overreacts to allergens in the air which results insneezing, rhinorrhea, itching, as well as sleep disturbance. According to the statistics, the prevalence of allergic rhinitis has increased globallyThe use of HMB-FA supplement to reduce the process of proteolysis and increase muscle mass is extremely common among athletes.Therefore, in this study, response of muscle damage indices to short-term supplementation of HMB-FA in professional soccer players wasinvestigated. A total of 24 professional soccer players were divided into two groups: supplement-sport (n=12) and placebo-sport (n=12).Both groups performed the simulated soccer protocol after receiving 3 d/g of HMB-FA supplement or placebo. Blood samples were taken tomeasure serum creatine kinase (CK) and lactate dehydrogenase (LDH) levels before the supplementation and immediately after the protocol.Data were analyzed using the covariance test at the level of (P <0.05). Intergroup comparison of data indicated that creatine kinase (CK) andlactate dehydrogenase (LDH) levels decreased significantly in the supplement group than in the placebo group (P<0.05). Examination ofintra-group changes of the CK index showed a significant difference between the mean before and after in both groups (P<0.05); however,in the LDH index there was only a significant difference between the mean before and after in placebo-exercise (P <0.05). The results of thisstudy showed that acute use of HMB-FA supplementation reduces CK and LDH as indices of muscle injury in professional soccer players.